Stormy, Misty's foal - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Aladdin Books ; Toronto : Collier Macmillan Canada ; New York : Maxwell Macmillan International Pub. Group, 1991)
A foal, born in the aftermath of a great storm, and her famous mother help raise money to repair the storm damage on Chincoteague Island and restore the herds of wild ponies on Assateague Island.
Keywords: Stormy -- (Horse) -- Fiction; Stormy (Horse) -- Juvenile fiction; Horses -- Juvenile fiction; Chincoteague pony -- Fiction; Ponies -- Fiction; Chincoteague Island (Va.) -- Fiction